Desarrollo de un método analítico por cromatografía iónica para la cuantificación de aniones en aguas residuales de origen minero - Cardona-Castaño, Julio-Andrés; Rivera-Giraldo, Juan-David; Chávez-Vallejo, Fernando-Antonio (Revista Científica, 2023)
The objective of this work was to develop a method by ion chromatography with conductivity detector for the simultaneous determination of thiocyanate in mining wastewater and anions such as bromide, chloride, fluoride, phosphate, nitrite, nitrate and sulfate. Potassium hydroxide (KOH) was used as an eluent in a range of concentrations between , flows between and suppressor current between . It was determined that the best separation of the species was achieved with a KOH concentration of in isocratic mode and a flow of in an AS20 analytical column. In addition, a series of analytical parameters such as sensitivity, linearity, precision, accuracy and limits of detection and quantification were determined that allow the validation of the analytical method. Relative standard deviation (RSD) values of less than 20 % were obtained in terms of the accuracy of the analytical method, with recoveries greater than 96 %. The method developed is therefore suitable for the determination of thiocyanate and anions in wastewater of mining origin.